2005
DOI: 10.3846/13923730.2005.9636357
|View full text |Cite
|
Sign up to set email alerts
|

Different Approaches of Clients and Consultants to Contractors’ Qualification and Selection

Abstract: Nowadays, clients are the dominant groups in almost all types of industries. However, the construction industry is unique and consultants, as representatives of clients, are very important figures in this industry as well. By presenting survey findings of 91 clients and 50 consultants, this study reveals clients’ and consultants’ differing expectations of contracting organisations during contractor qualification and selection. The study has clearly confirmed the fact that consultants’ perspectives are rather d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Wang et al (2013) discuss the best value method for contractor selection and applies Analytical Hierarchy Process (AHP) to weigh the decision criteria for selecting the best value contractors. Egemen and Mohamed (2006) discussed the clients' needs from contractors while Egemen and Mohamed (2005) focused on different approaches of clients and consultants in the contractor selection process. The study concluded that the expectations of clients and consultants from contractors varied significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al (2013) discuss the best value method for contractor selection and applies Analytical Hierarchy Process (AHP) to weigh the decision criteria for selecting the best value contractors. Egemen and Mohamed (2006) discussed the clients' needs from contractors while Egemen and Mohamed (2005) focused on different approaches of clients and consultants in the contractor selection process. The study concluded that the expectations of clients and consultants from contractors varied significantly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choosing not to bid on a prospective project results in losing an opportunity to make a substantial profit, whereas entering into bid may improve the strength of a contractor in the industry and gain positive relationships with the client (Jarkas et al, 2014). Bidding for unsubstantial projects can result in huge losses that include the consumption of resources as well as time that might have been invested in more profitable projects, ultimately resulting in financial failure of the firm (Egemen & Mohamed, 2005). Surveys by previous scholars have identified some of the important factors in the bid/no-bid decision making (Li et al, 2020;Shokri-Ghasabeh & Chileshe, 2016) but little consensus is found on optimal or specific approach regarding the decision to bid.…”
Section: Introductionmentioning
confidence: 99%